Communication process, extension and adoption of technologies - Cadena-Iñiguez, Pedro; Guevara-Hernández, Francisco; Argüello-Aguilar, Raúl A.; Rendón-Medel, Roberto (Revista Mexicana de Ciencias Agrícolas, 2018)
This document addresses communication issues, as the basis for initiating an extension process, to achieve the ultimate goal of the adoption and management of innovation. These concepts are approached from an institutional perspective which denotes the transition from a vertical vision to a more participatory vision where the actors involved in bringing development to the rural environment take into account the conditions of the final recipients. The three concepts are closely linked in such a way that one cannot conceive that one is detached from the other and the final result must be the innovation of both components and processes.
Keywords: communication; extension; technology adoption